2015
DOI: 10.1007/s12070-015-0840-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Septal Correction on the Blood Pressure of Hypertensive Patients with Deviated Nasal Septum

Abstract: This study aims to evaluate the effect of septal correction on the blood pressure (BP) of patients with symptomatic nasal septal deviation and to assess whether a positive association exists between deviated nasal septum and hypertension. A prospective observational clinical study was conducted at Kempegowda Institute of Medical Sciences, Bangalore. Hundred adults, aged 18-40 years, with symptomatic nasal septal deviation, newly detected untreated hypertension (mean BP C140/90 mmHg), undergoing submucosal rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…23,25,26 Sub mucoperichondrial resection (SMR) operation and septoplasty provided qualitative and quantitative relief in upper airway obstruction associated cardiovascular symptoms. [27][28][29] In a regional study, Smitha et al demonstrated a mean systolic and diastolic blood pressure recording of 141.82 ± SD 1.70 mmHg and 91.04 ± SD1.21 mmHg, respectively. These recordings declined to mean systolic and diastolic blood pressure of 128.93 ± 8.60 mmHg and 85.05 ± 4.85 mm Hg respectively 12 months after nasal septal corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,25,26 Sub mucoperichondrial resection (SMR) operation and septoplasty provided qualitative and quantitative relief in upper airway obstruction associated cardiovascular symptoms. [27][28][29] In a regional study, Smitha et al demonstrated a mean systolic and diastolic blood pressure recording of 141.82 ± SD 1.70 mmHg and 91.04 ± SD1.21 mmHg, respectively. These recordings declined to mean systolic and diastolic blood pressure of 128.93 ± 8.60 mmHg and 85.05 ± 4.85 mm Hg respectively 12 months after nasal septal corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These recordings declined to mean systolic and diastolic blood pressure of 128.93 ± 8.60 mmHg and 85.05 ± 4.85 mm Hg respectively 12 months after nasal septal corrective surgery. 28 Reciprocally, effective management of hypertension decreases the risk of, myocardial infarction, stroke, chronic kidney disease and heart failure. Ozkececi et al, also confirmed that MPAP decreased and right ventricular function tended to recover after septoplasty operation.…”
Section: Discussionmentioning
confidence: 99%
“…The former included lacrimal probe and rinse to eliminate canalicular and tear duct obstruction. The latter included a detailed nasal endoscopy to determine whether there were nasal abnormalities such as high deviated septum, which might influence the surgery effect [ 12 ]. All the operations, including the last revision DCR, were performed by the same surgeon.…”
Section: Methodsmentioning
confidence: 99%
“…После септопластики систолическое артериальное давление было снижено [49]. Этот сценарий (исход) часто наблюдался у пациентов моложе 35 лет с идиопатической гипертензией [50].…”
Section: септопластикаunclassified